Assessment of the application "twist-off" method for determining the in situ compressive and flexural strengths in the fiber concrete - Mahmood Naderi (Journal of Structural and Construction Engineering, 2021)
Since the batching, transportation, pouring, compaction and curing of the specimens used in laboratory testing of concrete, either from these employed in real structures, the in-situ methods are needed for assessing the quality of existing concrete in structures. Among the tests with partial failure, the "twist-off" method is used for determining the strength of concrete both in the laboratory and in-situ. In this paper the use of “twist-off” method for determining the strength of three types of fibre concrete is presented. In total 234 concrete samples were prepared, using three types of fibre (steel, glass and polypropylene) and their strength were measured using both “twist-off” and “compression” testing. The results show that a strong linear correlation exists between the compressive strength and the failure modulus with the results of the "twist-off" test. Also, to study the pattern of stresses in concrete, glue and cylinder of the "twist-off" test and the pattern of the formation and expansion of the cracks in concrete samples during the test, nonlinear modeling and finite elements were carried out using Abaqus/CAE. The finite element analysis with consideration of the nonlinear shape functions for the elements in tension and pressure on concrete specimens with a strength of 40 MPa shows that, with the distance of at least 20 mm, the results of the "twist-off" test and dispersion are not affected.